1990
DOI: 10.1210/jcem-70-1-181
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Estrogen Receptors Are Increased by RU486 in Late Pregnant Rhesus Macaques but not after Spontaneous Labor*

Abstract: Progesterone withdrawal as a mechanism for parturition in primates is controversial. The progesterone antagonist RU486, given in late pregnancy to rhesus monkeys at a dose of 47 mmol/kg.day (20 mg/kg.day), causes an increase in uterine activity, but not the expected increase in amniotic fluid prostaglandins or cervical dilatation. We, therefore, studied the effect of RU486 on estrogen receptor (ER) localization and concentration in reproductive tract tissues in rhesus monkeys during late gestation and after sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 25 publications
4
34
0
Order By: Relevance
“…There were no changes of ER in the pregnant baboon myometrium associated with gestation and labor. This observation is consistent with previous reports in rhesus monkey myometrium analyzed by binding assay (Novy & Haluska 1994) and immunohistochemistry (Haluska et al 1990) and our own data obtained by RT-PCR (Wu et al 2000).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…There were no changes of ER in the pregnant baboon myometrium associated with gestation and labor. This observation is consistent with previous reports in rhesus monkey myometrium analyzed by binding assay (Novy & Haluska 1994) and immunohistochemistry (Haluska et al 1990) and our own data obtained by RT-PCR (Wu et al 2000).…”
Section: Discussionsupporting
confidence: 94%
“…We and others have clearly demonstrated that estradiol up-regulates ER expression and progesterone down-regulates ER expression in nonpregnant uterine tissues in sheep (Wu et al 1996b), mouse (Bergman et al 1992), rhesus monkey (Okulicz et al 1993) and a human breast cancer cell line (Cho et al 1991). In addition, the observation that uterine ERs are increased by the PR antagonist RU486 in late gestation in the pregnant rhesus monkey is another example of progesterone's suppressive effect on uterine ER (Haluska et al 1990). These results suggest that the control of uterine ER is dependent on the complex interplay of estrogen and progesterone.…”
Section: Discussionmentioning
confidence: 84%
“…To what extent glucocorticoid signaling is important in this model system is unknown. Estradiol increased synthesis of cervical-like tissue and progesterone opposed this effect, which may relate to progesterone inhibition of the ERa expression [67]. Last, we previously demonstrated that synthesis of cervical-like tissue was strongly dependent on cell nutritional environment, a mechanism that could relate to steroid hormonal environment [46,47].…”
Section: Three-dimensional Culture Of Cervical Fibroblastsmentioning
confidence: 88%
“…It is interesting to note that the glucocorticoid antagonist RU 486 is administered in the same single doses ( 2 mg/100 g b.w.) to humans [Lause et al, 19881 and Resus macaques (Haluska et al, 1990).…”
Section: Discussionmentioning
confidence: 99%